2020
DOI: 10.5507/bp.2018.079
|View full text |Cite
|
Sign up to set email alerts
|

The absence of high-risk human papillomavirus in Czech non-small cell lung cancer cases

Abstract: Aims. The purpose of our study was to examine the presence of human papillomavirus (HPV) DNA in Czech patients with non-small cell lung cancer (NSCLC). Methods. A highly sensitive quantitative polymerase chain reaction (qPCR) detecting the E6 gene of HPV16, 18, 31, and 56 was designed. The limit of detection was assessed using serial dilutions of HPV-positive plasmids. The qPCR was validated on a set of 402 cervical swabs where the qPCR, Cobas, and PapilloCheck methods were tested in parallel. Finally, qPCR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The primary search generated 34 potentially relevant articles, six of which met the inclusion criteria ( 32 - 37 ) (Supplemental Material (Supplementary material) ). Two studies ( 38 , 39 ) did not find HPV in NSCLC patients whether or not they had EGFR mutations, and therefore could not be included in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The primary search generated 34 potentially relevant articles, six of which met the inclusion criteria ( 32 - 37 ) (Supplemental Material (Supplementary material) ). Two studies ( 38 , 39 ) did not find HPV in NSCLC patients whether or not they had EGFR mutations, and therefore could not be included in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR primers and probes listed in Table 1 were synthesized by Generi Biotech Ltd. (Hradec Kralove, the Czech Republic). The qPCR analysis was performed using a Light Cycler 480 II (Roche Diagnostics, Mannheim, Germany) according to a previously described protocol [16].…”
Section: Methodsmentioning
confidence: 99%
“…When the HPV was analyzed by conducting a consensus PCR, only five out of one hundred and thirty-two (3.8%) samples were HPV-positive [ 106 ]. In the Czech Republic, Jaworek et al (2020) did not detect HPV in 80 primary NSCLCs by using qPCR [ 107 ]. In Bordeaux, France, Chaussade et al (2022) reported HPV incidence rate ratios (IRR) of 1.8 [1.4–2.2] in a cohort of HIV-positive patients with lung cancer (incidence rates for 100 000 people per year) [ 108 ].…”
Section: Epidemiology Of Hpv In Lung Cancermentioning
confidence: 99%